Sintonia de controladores robustos para amortecimento de oscilações utilizando enxame de partículas - Silva, Felipe Fernandes da (2018)
Due to the constant growth and technological advancement of the electrical system, emerged electromechanical oscillations inherent in its operation. These oscillations are responsible for causing instability to the system as they limit the ability to transmit power as well as increase the risk of non-scheduled stops. The main objective of this work is the damping of electromechanical oscillation in power systems of three areas, aiming to achieve the robust stability of the system. For this, it will be used techniques of analysis and design of controllers for multivariate systems in frequency domain, to investigate the feasibility of achieving robust control from decentralized controllers of reduced order. The selection of the most important input-output series for the system is imperative for the controllers applyed, to achieve robustness. For this, the techniques of metric analysis were used: matrix research and analysis of the singular values. The techniques of analysis were applied to a load-frequency system of three areas. The controller is type ∞ and the method of aplication in this work, to obtain th robust control os the system, was the particle swarm optimization (PSO). The results obtained are satisfactory due to the robustness of the control and the damping of the oscillations of the system.